Syariat Islam di Indonesia: Pergulatan antara Sakralitas dan Profanitas - Ahmad Faisal (Al-Ulum, 2019)
This article elaborates on the application of Islamic law in Indonesia, which always invites polemics. The root of the problem turns out to not only lead to epistemological issues, but also social and political issues. The author argues that Islamic law that gains legitimacy and justification in the Indonesian legal system must meet the epistemological and social-political criteria. Epistemologically, it is only natural that there is no single view of the Shari'a model that is intended to be applied whereas sociologically political Islamic law must consider more social, political and historical variables that influence the formation of the Indonesian Islamic legal system. The latter fact is a necessity given the fact that the appearance of Islamic law itself in various Islamic countries is not uniform. Changes that occur in the substantive plains of Islamic law are the result of the interaction between the ulama as legal formulators and the socio-political factors that surround them, including the political configuration of the state.